2020
DOI: 10.3389/fncel.2019.00583
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Knockdown of Sprouty2 and PTEN Promotes Axon Elongation of Adult Sensory Neurons

Abstract: Sprouty2 (Spry2) and phosphatase and tensin homolog deleted on chromosome 10 (PTEN) are both well-established regulators of receptor tyrosine kinase (RTK) signaling, and knockdown of Spry2 or PTEN enhances axon regeneration of dorsal root ganglia (DRG) neurons. The major role of Spry2 is the inhibition of the rat sarcoma RAS/extracellular signal-regulated kinase (ERK) pathway, whereas PTEN acts mainly as an inhibitor of the phosphoinositide 3-kinase (PI3K)/Akt pathway. In non-neuronal cells, Spry2 increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In this study, we found that miR-21 showed a significant negative correlation with its target gene, SPRY2, during PNI and the repair process. miR-21 can promote the repair of nerve fibers by directly targeting SPRY2 [ 40 ], and the knockout of SPRY2 can enhance axonal regeneration of DRG neurons [ 95 ]. However, its in-depth mechanisms need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that miR-21 showed a significant negative correlation with its target gene, SPRY2, during PNI and the repair process. miR-21 can promote the repair of nerve fibers by directly targeting SPRY2 [ 40 ], and the knockout of SPRY2 can enhance axonal regeneration of DRG neurons [ 95 ]. However, its in-depth mechanisms need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…All three are essential tumor suppressors promoting programmed apoptosis [ 79 , 80 , 81 ]. In particular, SPRY2 and PTEN act as inhibitors of the Ras/Raf/ERK and Pi3k/AKT/mTOR pathways [ 82 ]. Furthermore, PTEN is involved in the regulation of NGF.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of PTEN and SPRY 2 is crucial for the regulation of axonal outgrowth and SC migration and proliferation in homeostasis. During the acute phase of nerve injury, high levels of PTEN and SRPY2 are unfavorable [ 82 , 102 ]. Consequently, a reduction of these two proliferation-inhibitory proteins by the application of miR-21 or miR-221/222 is necessary to accelerate nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, miRNA-21 contained in rSC-EVs showed a 1.7-fold increase in ATP-treated rSC compared to non-treated rSC (Figure 4C). miRNA-21 targets various genes involved in the regulation of neurite elongation and axonal growth, such as PTEN, SPRY2, and TIMP3 (Duraikannu et al, 2019;Jamsuwan et al, 2020;Borger et al, 2022); therefore, we evaluated whether ATP-rSCderived EVs regulate the expression of these genes in DRG neurons. Indeed, we observed a 70% decrease in the expression of PTEN, a 15% decrease in the expression of SPRY2, and a 30% decrease in the expression of TIMP3 in neurons treated with ATP-rSC-derived EVs compared to neurons treated with control rSC-derived EVs (Figure 4D).…”
Section: The Enhanced Growth E Ect Of Extracellular Vesicles From Atp...mentioning
confidence: 99%